2021
DOI: 10.3390/ijms222111415
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effect of Copper (II) Complexes with Halogenated 1,3-Disubstituted Arylthioureas on Cancer and Bacterial Cells

Abstract: A series of eight copper (II) complexes with 3-(4-chloro-3-nitrophenyl)thiourea were designed and synthesized. The cytotoxic activity of all compounds was assessed in three human cancer cell lines (SW480, SW620, PC3) and human normal keratinocytes (HaCaT). The complexes 1, 3, 5, 7 and 8 were cytotoxic to the studied tumor cells in the low micromolar range, without affecting the normal cells. The complexes 1, 3, 7 and 8 induced lactate dehydrogenase (LDH) release in all cancer cell lines, but not in the HaCaT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…The stark cytotoxic activities of thiourea derivatives against various types of cancers make them valuable structural motifs. Likewise, to have an access to novel therapeutic metal-based anticancer drugs with profound cytotoxicity, it is frequent to combine pharmacophores with metals. Accordingly, various metal complexes exhibited potent antiproliferative activities and are in clinical use as anticancer drugs. , In the same context, copper complexes are of paramount importance as anticancer agents revealing promising in vitro and in vivo antiproliferative activities. , Therefore, combining thiourea pharmacophores with Cu­(II) became a very favorable approach for developing compounds with antitumor activities. , With the N -naphthoyl thiourea library in hand, attention was now turned toward testing it for cytotoxicity against a range of cancer cell lines. In addition, the antiproliferative activity of Cu-complex 11 will be examined.…”
Section: Resultsmentioning
confidence: 99%
“…The stark cytotoxic activities of thiourea derivatives against various types of cancers make them valuable structural motifs. Likewise, to have an access to novel therapeutic metal-based anticancer drugs with profound cytotoxicity, it is frequent to combine pharmacophores with metals. Accordingly, various metal complexes exhibited potent antiproliferative activities and are in clinical use as anticancer drugs. , In the same context, copper complexes are of paramount importance as anticancer agents revealing promising in vitro and in vivo antiproliferative activities. , Therefore, combining thiourea pharmacophores with Cu­(II) became a very favorable approach for developing compounds with antitumor activities. , With the N -naphthoyl thiourea library in hand, attention was now turned toward testing it for cytotoxicity against a range of cancer cell lines. In addition, the antiproliferative activity of Cu-complex 11 will be examined.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent antibacterial property of copper and cobalt for Gram positive and negative bacteria, 32,33 as well as, cytotoxicity activity for multiple cancer cell lines have been reported previously. 28 Previous study aimed to load different metal ions such as Ag + , Cu 2+ , Zn 2+ , Mn 2+ or Fe 2+ onto CSNPs, showed that antibacterial activity was signicantly enhanced by the metal ions loaded, except for Fe 2+ . Especially for CSNP loaded Cu 2+ , the MIC for E. coli 25922, S. choleraesuis ATCC 50020 and S. aureus 25923 were 21-42 times lower than that of Cu 2+ .…”
Section: Antibiotic Resistant Genes Expression Modulation By the Effe...mentioning
confidence: 99%
“…Some of these compounds were tested for their cytotoxicity against strains of breast, colon, and liver cancer cells and showed outstanding antitumor activity against breast cancer cells MCF7, inducing cell death by cellular apoptosis. Some studies show that the presence of halogens in the dithiocarbazate structures can considerably increase the biological activity ( Chrzanowska et al, 2021 ; da Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%